2010
DOI: 10.1111/j.1365-294x.2010.04699.x
|View full text |Cite
|
Sign up to set email alerts
|

Mites as biological tags of their hosts

Abstract: Movements and spatial distribution of host populations are expected to shape the genetic structure of their parasite populations. Comparing the genetic patterns of both interacting species may improve our understanding of their evolutionary history. Moreover, genetic analyses of parasites with horizontal transmission may serve as indicators of historical events or current demographic processes that are not apparent in the genetic signature of their hosts. Here, we compared mitochondrial variation in population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 54 publications
(128 reference statements)
1
27
0
1
Order By: Relevance
“…2010), but also to a higher frequency of multiple infections—e.g. with parasites originating from diverse genetic strains (Bruyndonckx et al. 2009, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…2010), but also to a higher frequency of multiple infections—e.g. with parasites originating from diverse genetic strains (Bruyndonckx et al. 2009, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, Bruyndonckx et al (2009Bruyndonckx et al ( , 2010 found hints of co-speciation even between European bats and their ectoparasitic mites (Guiller and Deunff 2010). On this smaller scale, patterns are not always as clear as demonstrated by a study on co-speciation patterns of nycteribiid bat flies and their host bats in Japan.…”
mentioning
confidence: 80%
“…; Bruyndonckx et al . ). Moreover, parasites can reveal nonreproductive contact between different host populations or even different host species (Bruyndonckx et al .…”
Section: Introductionmentioning
confidence: 97%